2022
DOI: 10.1111/psyp.14125
|View full text |Cite
|
Sign up to set email alerts
|

Bid outcome processing in Vickrey auctions: An ERP study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 106 publications
1
3
0
Order By: Relevance
“…The amplitudes of the N170 and P3 components, but not the RewP, were modulated by SV in both types of auctions, with greater amplitudes for high‐ than low‐value auction items. The insensitivity of the RewP to SV as dictated by bid value is in line with findings from our previous VA study, where the RewP was indifferent to the market value of the auction items (Newton‐Fenner et al, 2022 ). The more positive P3 amplitude potentials following high SV outcomes compared to low SV items may be linked to attentional engagement (Nieuwenhuis, Aston‐Jones, et al, 2005; San Martin, 2012 ; Yeung & Sanfey, 2004 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The amplitudes of the N170 and P3 components, but not the RewP, were modulated by SV in both types of auctions, with greater amplitudes for high‐ than low‐value auction items. The insensitivity of the RewP to SV as dictated by bid value is in line with findings from our previous VA study, where the RewP was indifferent to the market value of the auction items (Newton‐Fenner et al, 2022 ). The more positive P3 amplitude potentials following high SV outcomes compared to low SV items may be linked to attentional engagement (Nieuwenhuis, Aston‐Jones, et al, 2005; San Martin, 2012 ; Yeung & Sanfey, 2004 ).…”
Section: Discussionsupporting
confidence: 90%
“…The P3 is also sensitive to outcome magnitude, with larger rewards/losses eliciting greater amplitudes (Bellebaum & Daum, 2008 ; Yeung & Sanfey, 2004 ). Relevantly, in our most recent study using a VA task, auction outcomes were associated with larger P3 amplitudes for high‐market value than low‐market value items, and win outcomes compared to no‐win outcomes (Newton‐Fenner et al, 2022 ). Similarly, Tyson‐Carr et al ( 2018 ) also found during a BDM task that high‐value products produced increased activation in the P3 interval during the initial valuation period.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…It should be acknowledged that the BDM has been found to be not incentive compatible in certain circumstances, such as when the object being valued is a lottery [158]. Furthermore, there is evidence that bid values in secondprice sealed bid auctions can be impacted by subjective perceptions of uncertainty [159] and social competition [160]. Furthermore, the decision to focus on the BDM task, while allowing a clean analysis of SV computation without the confounding effects of task heterogeneity, resulted in a smaller final cohort.…”
Section: Plos Onementioning
confidence: 99%